Prevalence of COVID-19 anxiety in division I student-athletes - Sanborn, V.; Todd, L.; Schmetzer, H.; Manitkul-Davis, N.; Updegraff, J.; Gunstad, J. (Journal of Clinical Sport Psychology, 2021)
Anxiety and depressive symptoms are prevalent in athletes. The pandemic of novel coronavirus (COVID-19) may increase risk for symptoms due to fear of exposure during competition or uncertainty regarding participation. The current study examined the prevalence of COVID-19 anxiety in 437 National Collegiate Athletic Association Division I student-athletes and its association with psychological symptoms. Only 0.2% of participants endorsed COVID-19 anxiety symptoms above cutoff. COVID-19 anxiety did not change after postponement of fall sports or differ between persons competing in different seasons. However, higher levels of COVID-19 anxiety were significantly associated with depression, anxiety, and stress. Though student-athletes generally reported low levels of psychological symptoms, females endorsed significantly higher levels than males. Low levels of COVID-19 anxiety in student-athletes may reflect protective factors (e.g., health knowledge, emotion regulation) or the tendency for this population to minimize psychological symptoms. Further investigations on the psychological impact of COVID-19 in athletes is needed.